2016
DOI: 10.4209/aaqr.2016.06.0224
|View full text |Cite
|
Sign up to set email alerts
|

Control of Bioaerosols in Indoor Environment by Filter Coated with Nanosilicate Platelet Supported Silver Nanohybrid (AgNPs/NSP)

Abstract: Currently silver nanoparticles (AgNP)-modified filter are widely used to inactivate airborne microbes in indoor environment. However, AgNP is extremely small and thus will penetrate cells membranes to cause cytotoxicity. AgNPs/NSP has been proven to be less cytotoxic to human body. In this study, it was the first time that AgNPs/NSP was used to develop a new antimicrobial air filter with low cytotoxicity. The AgNPs/NSP filter was made by dip-coating of filter with AgNPs/NSP and acrylic resin solution and three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
0
15
1
Order By: Relevance
“…Nanoparticles of silver (Ag) [ 178 180 ], silver compounds (Ag + ) [ 181 ], titanium dioxide (TiO 2 ) [ 182 , 183 ], zinc oxide (ZnO) [ 184 186 ], and aluminum and aluminum oxide (Al 2 O 3 ) [ 187 ] have been incorporated to various filters for antimicrobial properties. A synergistic antimicrobial performance is also revealed via their combination with other biocidal agents, such as carbon nanotubes [ 178 , 180 , 181 ]. Apart from antimicrobial air filters, multifunctional air filters, which simultaneously remove PM, microorganisms, and volatile organic compounds (VOCs), have drawn increasing research attention recently [ 188 , 189 ].…”
Section: Engineering Of Multifunctional Masks and Mask Materialsmentioning
confidence: 99%
“…Nanoparticles of silver (Ag) [ 178 180 ], silver compounds (Ag + ) [ 181 ], titanium dioxide (TiO 2 ) [ 182 , 183 ], zinc oxide (ZnO) [ 184 186 ], and aluminum and aluminum oxide (Al 2 O 3 ) [ 187 ] have been incorporated to various filters for antimicrobial properties. A synergistic antimicrobial performance is also revealed via their combination with other biocidal agents, such as carbon nanotubes [ 178 , 180 , 181 ]. Apart from antimicrobial air filters, multifunctional air filters, which simultaneously remove PM, microorganisms, and volatile organic compounds (VOCs), have drawn increasing research attention recently [ 188 , 189 ].…”
Section: Engineering Of Multifunctional Masks and Mask Materialsmentioning
confidence: 99%
“…8,9 Filters can be pre-treated with antibacterial agents (e.g. tea tree oil, 10 silver nanoparticles 11 or flavonoids 12 ) to inactivate microorganisms. Another method for protecting filter surfaces from microorganisms involves combining HEPA filters with photocatalytic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Bioaerosols generated from airborne particles of biological origin include fungi, bacteria, viruses, and fragments of the foregoing or their metabolic products (e.g., endotoxins, mycotoxins) (Chow et al, 2015;Walser et al, 2015;Chen et al, 2016;Zhang et al, 2016;Lal et al, 2017). Environmental health studies have indicated that constant exposure to bioaerosols containing high concentrations of bacteria can lead to respiratory diseases including allergies, infections, and other adverse health effect (Bünger et al, 2007;Lu et al, 2016;Mirhoseini et al, 2016).…”
Section: Introductionmentioning
confidence: 99%